Opportunities and challenges for the development of second-generation biofuels in developing countries: A case of agave-based biogas from the Mezcal industry in Oaxaca, Mexico - GONZALEZ, MARIA DEL CARMEN (2017)
This paper identifies the technological, commercial, organizational and social opportunities and challenges related with the development and implementation of the agave-based biogas from the Mezcal industry in Oaxaca, Mexico, under the light of the technological, commercial, organizational and social uncertainties framework by Martin and Hall for innovation management. First generation biofuels like ethanol and biodiesel have been constantly debated for the social and environmental issues derived from its production and commercialization. Second-generation biofuels instead, have gained interest in developed and developing countries for their so promoted multiple social and environmental benefits. The biogas technology, a second generation biofuel, has been promoted in several countries for its multiple advantages, however it has been challenged by multiple barriers. Based on the perspectives of multiple stakeholders, the agave-based biogas technology from the Mezcal industry in Oaxaca, Mexico seems to be challenged by political, environmental and technical uncertainties but also technical and social opportunities to develop